Eriophyoid mites (Acari: Trombidiformes: Eriophyoidea) of Rosales trees in Iran: two new species and three new records - Lotfollahi, Parisa; Irani-Nejad, Karim Haddad; Lillo, Enrico De (Zootaxa, 2014)
This paper describes two new species of Eriophyoidea associated with trees belonging to the order Rosales in the south-western portion of East Azerbaijan province, Iran, collected during a survey in 2011: Aceria lobolinguae n. sp. on Elaeagnus angustifolia L. (Elaeagnaceae) and Rhinophytoptus nemalobos n. sp. on Prunus domestica L. (Rosaceae). Additionally, Phyllocoptes abaenus Keifer on Prunus armeniaca L. (Rosaceae), Aculus fockeui (Nalepa & Trouessart) on Prunus amygdalus Stokes and Malus domestica Borkh. (Rosaceae), and Aceria mori (Keifer) on Morus alba L. (Moraceae) were collected and are new records for the mite fauna of Iran. New locality records and host plant data are provided for Eriophyes similis (Nalepa), Eriophyes pyri (Pagenstecher) and Calepitrimerus baileyi (Keifer) which are eriophyoid species previously known from Iran.